Investigation of ionic liquids as a pretreatment solvent for extraction of collagen biopolymer from waste fish scales using COSMO-RS and experiment - Muhammad, N. (Elsevier B.V., 2017)
Collagen being an abundant natural biopolymer and also has many applications for bio-medical and non-biomedical uses, were extracted from waste fish scales using green route of ionic liquid pretreatment. To get insight on dissolution and extraction of collagen from fish scale using ionic liquids, COSMO-RS computational approach was used to identify the best ionic liquid. The 1-ethyl-3-methylimidazolium acetate (C2C1imAc) ionic liquid based on low activity coefficient (inverse of solubility) and best fit sigma profile was selected for pretreatment. The ground fish scales were pretreated with C2C1imAc ionic liquid and further subjected to separation for obtaining the collagen. The collagen was obtained in the form of thin film with yield of 3.1 ± 0.5% at 100 °C for 12 h treatment time. The obtained collagen was characterized using Fourier Transform Infrared Spectroscopy (FTIR), UV–Vis spectrometer, Powder X-rays Diffraction (PXRD), Thermal Gravimetric Analysis (TGA), Field Emission Scanning Microscopy (FE-SEM), Energy Dispersive X-rays spectroscopy (EDX). The FTIR, UV–Vis and XRD analysis shows the characteristic peaks assigned to the collagen. The SEM analysis confirms the dissolution of collagen fibers in ionic liquid. The TGA analysis shows lower thermal stability of extracted collagen as compared to fish scales. © 2017 Elsevier B.V.